Tanggung Jawab Negara terhadap Pelanggaran Ruang Udara yang Dilakukan Balon Udara - Naza Muhammad Zakwan; Iman Sunendar (Jurnal Riset Ilmu Hukum, 2023)
Abstract. This research is motivated by a violation of sovereignty in airspace by hot air balloons. Each country has full and exclusive sovereignty over the air space above its territory as regulated in Article 1 of the 1944 Chicago Convention. Any country that violates state sovereignty will incur state responsibility. This study aims to understand how hot air balloons are positioned according to the 1944 Chicago Convention and what state responsibility is for violations of airspace by hot air balloons according to the 1944 Chicago Convention. This research uses normative juridical methods, with library data or secondary data which includes primary, secondary legal materials , and tertiary. The results obtained are: (1) The position of the hot air balloon is an aircraft regulated in Appendix 2 of the 1944 Chicago Convention and the hot air balloon is included in an aircraft that is lighter than air. Unmanned free balloons can only be flown under certain conditions listed in Appendix 4 Point 2 (General Operating Rules) in Annex 2 Rules of The Air. Therefore, every country that flies its hot air balloon has the obligations contained in the 1944 Chicago Convention. (2) In the context of civil anger, the country that experienced the violation is not allowed to take unlimited countermeasures such as the use of weapons. Airspace violations committed by state aircraft will incur the responsibility of the violating state. Some of these forms of accountability include an apology, a promise to punish the individual responsible, a promise not to repeat the violation, as well as other sanctions such as the seizure of the offender's plane and the imprisonment of the flight crew. Keywords: Violation of air space, Hot air balloon, State responsibility Abstrak. Penelitian ini dilatar belakangi oleh adanya pelanggaran kedaulatan di ruang udara oleh balon udara. Setiap negara memiliki kedaulatan penuh dan eksklusif atas ruang udara di atas wilayahnya itu diatur dalam Pasal 1 Konvensi Chicago 1944. Setiap negara yang melanggar kedaulatan negara akan menimbulkan tanggung jawab negara. Penelitian ini bertujuan untuk memahami bagaimana kedudukan balon udara menurut Konvensi Chicago 1944 serta bagaimana tanggung jawab negara atas pelanggaran ruang udara oleh balon udara menurut Konvensi Chicago 1944. Penelitian ini menggunakan metode yuridis normatif, dengan data kepustakaan atau data sekunder yang mencakup bahan hukum primer, sekunder, dan tersier. Hasil yang diperoleh yakni: (1) Kedudukan balon udara merupakan pesawat udara diatur dalam annex 2 Konvensi Chicago 1944 dan balon udara termasuk kedalam pesawat udara yang lebih ringan dari udara. Unmanned free balloon hanya dapat diterbangkan dalam kondisi tertentu terdapat pada Appendix 4 Point 2 (General Operating Rules) dalam Annex 2 Rules of The Air. Maka dari itu setiap negara yang menerbangkan balon udaranya memiliki kewajiban yang tertuang didalam Konvensi Chicago 1944. (2) Dalam konteks penerbangan sipil, negara yang mengalami pelanggaran kedaulatannya tidak diperbolehkan mengambil tindakan balasan yang tidak terbatas seperti penggunaan senjata. Pelanggaran ruang udara yang dilakukan oleh pesawat negara akan menimbulkan tanggung jawab negara pelanggar. Beberapa bentuk pertanggungjawaban tersebut antara lain permintaan maaf, janji untuk mempidanakan individu yang bertanggung jawab, janji untuk tidak mengulangi pelanggaran, serta sanksi-sanksi lainnya seperti perampasan pesawat pelanggar dan pemenjaraan awak pesawat. Kata Kunci: Pelanggaran ruang udara, Balon udara, Tanggung jawab negara